Effect of prebiotic oligosaccharides on growth of Lactobacillus strains used as a probiotic for chickens - Poothan Mookiah, Saminathan; Sieo, Chin Chin; Ramasamy, Kalavathy; Abdullah, Norhani; Ho, Yin Wan (Academic Journals, 2011)
In the present study, the effect of 10 commercially available oligosaccharides on the growth of 11 Lactobacillus strains, which were isolated from the gastrointestinal tract of chickens and have been used as a multistrain probiotic for chickens, was evaluated in vitro. The utilization of oligosaccharides was highly variable among the 11 Lactobacillusstrains and considerable strains differences (P < 0.05) were observed. Isomaltooligosaccharides (IMO) supported good growth for all the 11 Lactobacillus strains, followed by galactooligosaccharides (GOS), gentiooligosaccharides (GTO) and fructooligosaccharides (FOS). Oligosaccharides such as Raftilose L60, Raftilose P95, Raftiline LS, and mannanoligosaccharides (MOS) were poorly utilized by all theLactobacillus strains. Growth kinetics study also showed variations in the specific growth rates and growth patterns of four representative Lactobacillus species on four selected oligosaccharides. The highest specific growth rate was demonstrated by Lactobacillus salivarius I 24 on FOS. The results showed that the ability of the 11 probiotic Lactobacillusstrains to utilize oligosaccharides could be both strain and substrate specific, which demonstrates the importance of selecting suitable prebiotic oligosaccharides for the preparation of synbiotics.